Termination of Prosecutions Based On Restorative Justice in The Settlement of Criminal Cases In The Area of The High Prosecutors Of Lampung - Yuris Oktaviyani Citizen (Fakultas Hukum Universitas Lampung, 2022)
The Attorney General's Office of the Republic of Indonesia has issued a breakthrough in efforts to resolve cases through the termination of prosecution based on restorative justice. The Prosecutor's Office of the Republic of Indonesia, a law enforcement officer referred to as a case controller based on the dominus litis principle has a significant role in determining the success of applying restorative justice in Indonesia. Therefore, this article examines and analyzes the implementation and inhibiting factors for stopping prosecutions based on restorative justice in settlement of criminal cases in the Lampung High Court area. The research method in writing this paper uses a normative juridical and empirical juridical approach, with 6 (six) sources from academics and the Public Prosecutor in the Lampung High Prosecutor's Office. The data is then processed and analyzed cumulatively. Based on the research results, the Lampung High Court has adopted the termination of restorative justice-based prosecutions in three (three) District Attorney's Offices. Meanwhile, the obstacle to stopping restorative justice-based prosecutions in the Lampung High Court area is dominated by overlapping arrangements for implementing restorative justice between law enforcement agencies, namely the Prosecutor's office and the police, which legal uncertainty and lead to disparities in law enforcement and the lack of community participation, especially among victims.